Efeito de diferentes agentes naturais biomodificadores na adesão à dentina hígida e afetada por cárie - Lemos, Marcelo Victor Sidou (2016)
Minimally invasive dentistry has been prioritizing more conservative cavity preparations. For this reason, the employment of strategies as dentin biomodification, to ameliorate the mechanical properties of resin-dentin interface and to protect collagen fibrils from biodegradation, is highlighted as a promising technique. The present study aimed to evaluate the influence of different natural biomodification agents on resin-dentin bond strength, nanoleakage and micropermeability at sound and caries-affected dentin. The variable investigated were (1) dentin pre-treatment: absolute ethanol (control), proanthocyanidins (PACs) 2%, cardol (from cashew nut shell liquid) 2%, cardol-methacrylate 2%, cardanol-methacrylate 2% and epigallocatechin-3-gallate (EGCG) 0.1%; and (2) dentin substrate: sound dentin and artificial caries-affected dentin. Microtensile bond strength (n=6), dentin micropermeability (n=3) and interfacial nanoleakage (n=6) were assessed on a universal testing machine, confocal-laser scanning microscope and scanning electron microscope respectively. The bond strength on sound dentin was higher by using cardol-methacrylate and EGCG. On caries-affected dentin, pre-treatment using cardol-methacrylate achieved the highest bond strength. All biomodification agents reduced the nanoleakage in comparison with control, except cardanol-methacrylate. On sound dentin, the micropermeability was decreased when using cardanol- and cardol-methacrylate. Cardol-methacrylate has shown to be a promising biomodification agent thereby improving dentin bonding at both sound and caries-affected dentin.